The MEK-Inhibitor Selumetinib Attenuates Tumor Growth and Reduces IL-6 Expression but Does Not Protect against Muscle Wasting in Lewis Lung Cancer Cachexia - Au, Ernie D.; Desai, Aditya P.; Koniaris, Leonidas G.; Zimmers, Teresa A. (Frontiers in Physiology, 2017)
Cachexia, or wasting of skeletal muscle and fat, afflicts many patients with chronic diseases including cancer, organ failure, and AIDS. Muscle wasting reduces quality of life and decreases response to therapy. Cachexia is caused partly by elevated inflammatory cytokines, including interleukin-6 (IL-6). Others and we have shown that IL-6 alone is sufficient to induce cachexia both in vitro and in vivo. The mitogen-activated protein/extracellular signal-regulated kinase kinase (MEK) inhibitor Selumetinib has been tested in clinical trials for various cancers. Moreover, Selumetinib has also been shown to inhibit the production of IL-6. In a retrospective analysis of a phase II clinical trial in advanced cholangiocarcinoma, patients treated with Selumetinib experienced significant gains in skeletal muscle versus patients receiving standard therapy. However, the use of Selumetinib as a treatment for cachexia has yet to be investigated mechanistically. We sought to determine whether MEK inhibition could protect against cancer-induced cachexia in mice. In vitro, Selumetinib induced C2C12 myotube hypertrophy and nuclear accretion. Next we tested Selumetinib in the Lewis lung carcinoma (LLC) model of cancer cachexia. Treatment with Selumetinib reduced tumor mass and reduced circulating and tumor IL-6; however MEK inhibition did not preserve muscle mass. Similar wasting was seen in limb muscles of Selumetinib and vehicle-treated LLC mice, while greater fat and carcass weight loss was observed with Selumetinib treatment. As well, Selumetinib did not block wasting in C2C12 myotubes treated with LLC serum. Taken together, out results suggest that this MEK inhibitor is not protective in LLC cancer cachexia despite lowering IL-6 levels, and further that it might exacerbate tumor-induced weight loss. Differences from other studies might be disease, species or model-specific.